Load distribution for composite steel–concrete horizontally curved box girder bridge. (January 2016) - Fatemi, S.J.; Mohamed Ali, M.S.; Sheikh, A.H.
Abstract: A comprehensive numerical investigation is carried out to assess the load distribution mechanism of horizontally curved steel–concrete composite box girder bridges when subjected to loading recommended by Australian Bridge Design Code and American Association of State Highway and Transportation Officials (AASHTO). In this investigation, the effect of various parameters such as curvature ratio, span length, number of loading lanes and number of cells is considered. In addition, a convergence study is carried out to identify the appropriate bracing system so as to retain the maximum torsional rigidity of these structures. The numerical model is first validated with actual test results so that they can be adopted for an extensive parametric study with good confidence. The results obtained from the parametric study are used to determine load distribution factors for moment and shear of horizontally curved box girder bridges. It is observed that these load distribution factors according to AASHTO loads are considerably higher than those obtained from the loading recommended by Australian Bridge Design Code. Hence, it is not reasonable to use load distribution factor based on AASHTO loading guidelines for the design of these curved bridges subjected to Australian Bridge Design loading. Highlights: Load distribution factors (LDFs) of curved bridges are determined. Curvature ratio and number of cells have significant effects on LDFs for bending moment. The maximum spacing of the cross brace spacing should be not more than 5 m. LDFs for both bending moment and shear force of a curved bridge are greater than those for a straight bridge.